2010
DOI: 10.1177/155698451000500606
|View full text |Cite
|
Sign up to set email alerts
|

Video-Assisted Minimally Invasive Mitral Valve Surgery External Aortic Clamp versus Endoclamp Techniques

Abstract: Objective Video-assisted minimally invasive mitral valve surgery can be performed through different approaches. The aim of the study was to report our early results and compare the external transthoracic aortic clamping with the endoaortic balloon occlusion techniques according to our experience. Methods Between January 2000 and March 2010, 138 patients (103 women, aged 58.4 ± 10.2 years) underwent video-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
(32 reference statements)
2
28
0
Order By: Relevance
“…Several smaller reports have demonstrated the safety of the endoaortic balloon [16,[22][23][24]. Our large experience corroborates these findings.…”
Section: Commentsupporting
confidence: 90%
“…Several smaller reports have demonstrated the safety of the endoaortic balloon [16,[22][23][24]. Our large experience corroborates these findings.…”
Section: Commentsupporting
confidence: 90%
“…Previous studies, with relatively small groups, showed that EAC compared with EAB performs equally in terms of safety and the low risk of morbidity and mortality. These studies describe a longer procedure time, CPB time and cross-clamp (CX)-time when the EAB-technique is compared with EAC-technique [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…According to the recent literature other institutions see an advantage in aortic endoclamping, particularly in reoperations, to reduce blood in the field and avoid the need to operate on the fibrillating heart. According to their data, no specific complications related to the endoclamping techniques have been observed and equal outcomes have been reported when compared with external aortic clamping 10 11…”
Section: Setupmentioning
confidence: 99%